Pengaruh Independensi, Kompetensi dan Gaya Kepemimpinan Terhadap Kinerja Auditor Internal Pemerintah - Soraya Annisa Nasution; Agustiawan Agustiawan; Della Hilia Anriva (Politeknik Negeri Bengkalis, 2022)
This research aims to analyze partially and simultaneously the effect of independence, competence, and leadership style on the performance of the government’s internal auditors at Badan Pengawas Keuangan dan Pembangunan (BPKP) and the Inspectorate of Riau Province. This research is a quantitative descriptive type. The data source used is primary data. Data was collected by survey approach using a questionnaire method. The population in this research were all auditors at BPKP and the Inspectorate of Riau Province. The research sample is the entire population used in the study. Sampling was carried out using the saturated/census sampling method. The analytical technique used is multiple linier regression analysis and processed using SPSS 25 version software. The partial result shows that independence has no significant effect on auditor performance, competence has a significant effect on auditor performance and leadership style has a significant effect on auditor performance.Keywords: Independence, Competence, Leadership style, Auditor performance